E-cigarette or Vaping Product Use-Associated Lung Injury (EVALI) and Other Known Consequences of E-Cigarette Use – A Literature Review - Kaszyńska, Karolina; Balik, Dominik; Dąbek, Jakub; Grabowska, Karolina; Grabowska, Martyna; Kosucka, Wiktoria; Kubicka, Jagoda; Kwaśniewska, Anna; Lara, Joanna; Wiśniewska, Aleksandra (Journal of Education, Health and Sport, 2025)
Introduction and Purpose: E-cigarettes, introduced to the market at the beginning of the 21st century, have become a popular alternative to traditional cigarettes, though their long-term health effects remain unknown. In 2019, the United States recorded a sudden surge in cases of e-cigarette or vaping product use-associated lung injury (EVALI) - a severe lung disease linked to the use of these products. The aim of the study is to review the current knowledge on E-cigarette or vaping product use-associated lung injury (EVALI), with particular emphasis on pathogenesis, clinical presentation, and diagnostic and therapeutic challenges. State of knowledge: EVALI is primarily associated with the inhalation of vitamin E acetate (VEA), used as a thickener in illegal THC liquids. Pathogenetic mechanisms include toxicity from thermal degradation products of VEA leading to destabilization of pulmonary surfactant. The disease manifests with a broad spectrum of symptoms: dyspnea (85–100%), cough (60–85%), fever (57–84%), and gastrointestinal complaints (nausea, vomiting). Diagnosis requires the exclusion of infections (including COVID-19) and is based on CDC criteria, encompassing changes in lung imaging studies and a history indicating e-cigarette use. Conclusions: EVALI remains a public health challenge, particularly among young adults. Despite progress in identifying VEA as a key risk factor, many questions remain unanswered – including the role of other liquid components (e.g., flavoring substances) and the long-term effects of the disease. Further research is needed on the standardization of treatment (including the use of glucocorticosteroids) and regulation of the e-cigarette market. EVALI prevention should focus on educating about the risks of using products from illegal sources and promoting complete cessation of vaping. Keywords: EVALI; e-cigarette or vaping-associated lung injury; vaping; e-cigarette; vitamin E acetate; VEA.